The Strategic Role of Social Entrepreneurship in Addressing Communal Conflicts in Indonesia - Hana Putra; Djayeng Tirto; Bambang Wahyudi; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research examines the strategic role of social entrepreneurship in the resolution of communal conflicts in Indonesia, focusing on its use as a tool for mediation and community recovery. Utilizing qualitative methodologies and documentary studies, this study collects and analyzes data on how social entrepreneurship initiatives contribute to peacebuilding and social integration. The findings indicate that social entrepreneurship not only plays a role in generating economic profits but also promotes social coherence and improves the quality of life in communities affected by conflicts. This study also evaluates the challenges in the implementation of social entrepreneurship and provides practical recommendations for the development of policies and practices that support social integration and national stability. Consequently, this study offers valuable insights into the potential of social entrepreneurship as an effective tool in resolving communal conflicts in Indonesia